The Role of Restorative Justice in Handling Corruption Crimes - H Yusep Mulyana; Andi Kurniawan (Ipso Jure, 2025)
Restorative justice is an alternative approach in the criminal justice system that focuses on recovering losses due to criminal acts, including corruption. This approach emphasizes the involvement of perpetrators, victims, and the community in finding fair solutions and prioritizing recovery for the impacts caused. This study discusses the role of restorative justice in dealing with corruption crimes by analyzing its effectiveness, challenges, and application in the legal system in Indonesia. With a juridical-normative method and a qualitative approach, this study finds that restorative justice can be an instrument that complements the retributive approach, especially in the recovery of state assets and the prevention of repeated corruption. However, its implementation faces obstacles in the form of regulations that are not comprehensive and resistance in the application of restorative justice for corrupt actors. This study emphasizes the importance of policies that support the application of restorative justice in corruption cases to increase the effectiveness of law enforcement and provide broader benefits to society and the state.